2020
DOI: 10.1002/jbm.b.34607
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two pore sizes of LAE442 scaffolds and their effect on degradation and osseointegration behavior in the rabbit model

Abstract: The magnesium alloy LAE442 emerged as a possible bioresorbable bone substitute over a decade ago. In the present study, using the investment casting process, scaffolds of the Magnesium (Mg) alloy LAE442 with two different and defined pore sizes, which had on average a diameter of 400 μm (p400) and 500 μm (p500), were investigated to evaluate degradation and osseointegration in comparison to a ß‐TCP control group. Open‐pored scaffolds were implanted in both greater trochanter of rabbits. Ten scaffolds per time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…For cancellous bone at the same location, the Th 142 was determined using µCT scans of both lateral femoral condyles of adult Zika rabbit cadavers ( n = 4) with intact femurs. Scaffold volume (SV) and scaffold surface area to volume ratio (SS/SV) were calculated following the studies of Kowalewicz et al (2021) , Augustin et al (2020) , and Kleer et al (2019) in a region of interest (ROI) in the scaffold center. This ROI included a cylinder with a diameter of 140 voxels (≙4.24 mm) and a height of 60 slices (≙1.82 mm) ( Figures 1C,D ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For cancellous bone at the same location, the Th 142 was determined using µCT scans of both lateral femoral condyles of adult Zika rabbit cadavers ( n = 4) with intact femurs. Scaffold volume (SV) and scaffold surface area to volume ratio (SS/SV) were calculated following the studies of Kowalewicz et al (2021) , Augustin et al (2020) , and Kleer et al (2019) in a region of interest (ROI) in the scaffold center. This ROI included a cylinder with a diameter of 140 voxels (≙4.24 mm) and a height of 60 slices (≙1.82 mm) ( Figures 1C,D ).…”
Section: Methodsmentioning
confidence: 99%
“…This ROI included a cylinder with a diameter of 140 voxels (≙4.24 mm) and a height of 60 slices (≙1.82 mm) ( Figures 1C,D ). Bone volume (BV), trabecular number (Tb.N), trabecular thickness (Tb.Th), and trabecular separation (Tb.Sp) in the scaffold environment were calculated also based on the studies of Kowalewicz et al (2021) , Augustin et al (2020) and Kleer et al (2019) in a second hollow cylindrical ROI (inner ring: Ø = 144 voxel (≙4.36 mm), outer ring: Ø = 180 voxel (≙5.45 mm), height = 60 slices) ( Figure 1E ). To establish reference values for cancellous bone, the cancellous part of both femoral condyles of cadavers of adult Zika rabbits ( n = 4) with intact femora was examined.…”
Section: Methodsmentioning
confidence: 99%
“…Flatley et al reported that 500 μm pores were the optimum size for osteoconduction . Augustin et al implanted magnesium alloy LAE442 scaffolds with different pore sizes in rabbit femurs and ultimately observed significantly better osseointegration with a 500 μm pore size than with a 400 μm pore size . Considering these factors, we ultimately selected the pore sizes mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…25 Augustin et al implanted magnesium alloy LAE442 scaffolds with different pore sizes in rabbit femurs and ultimately observed significantly better osseointegration with a 500 μm pore size than with a 400 μm pore size. 26 Considering these factors, we ultimately selected the pore sizes mentioned above. The expression of the MyD88 protein, the key factor in the classic TLR4/MyD88/NF-kappa B pathway of macrophage polarization, 27 was quantitatively analyzed using immunohistochemical (IHC) staining to understand the potential mechanism by which the pore size of 3D-printed scaffolds affects macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…24,38 So far only solid LAE442 implants have been investigated [2][3][4]11,[18][19][20]39 and have achieved promising results with regard to peri-implant bone formation. 2,3,5,11,[18][19][20] LAE442 was used the first time in the form of open-pored scaffolds, with two firmly defined and always homogeneously reproducible pore size models in the study by Augustin et al 40 Associated investigations on the clinical tolerability as well as µCT measurements of the outer scaffold and bone environment provided promising results. Using high-resolution ex vivo µCT80 scan images, SEM/ EDX images, and histological tissue samples, the objective of the present study was to investigate which pore size model is more suitable as an osteoconductive and therefore potentially more suitable bone substitute for osteoneogenesis.…”
Section: Introductionmentioning
confidence: 99%